2008
DOI: 10.1016/j.memsci.2007.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Medical applications of membranes: Drug delivery, artificial organs and tissue engineering

Abstract: This paper covers the main medical applications of artificial membranes. Specific attention is given to drug delivery systems, artificial organs and tissue engineering which seem to dominate the interest of the membrane community this period. In all cases, the materials, methods and the current state of the art are evaluated and future prospects are discussed. Concerning drug delivery systems, attention is paid to diffusion controlled systems. For the transdermal delivery systems, passive as well as iontophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
236
1
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(245 citation statements)
references
References 291 publications
(296 reference statements)
0
236
1
8
Order By: Relevance
“…[37][38][39][40][41] The purpose of the present study is to systematically incorporate specific excipients into TR-loaded PLGA in situ gel formulations in order to evaluate the burst effect in vivo. The hot-plate test was administered to mice to assess their response to TR release.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…[37][38][39][40][41] The purpose of the present study is to systematically incorporate specific excipients into TR-loaded PLGA in situ gel formulations in order to evaluate the burst effect in vivo. The hot-plate test was administered to mice to assess their response to TR release.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The principle consists in carrying insulin secretory cells/islets from human or animal origins in order to physiologically respond to the patient's body needs in terms of insulin (Ludwig et al, 2013). Such devices are composed of living cells held within porous membranes that protect them from organisms such as antibodies which can destroy them (Dulebohn et al, 2014), and have porosities that allow some hormones and biomolecules to pass through (Stamatialis et al, 2008). This makes it possible to transplant cells for the endocrine regulation without the need of immunosuppressive drugs (Benhamou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane-based systems have been used for both passive and iontophoretic TDDS (Kost and Langer, 2001;Stamatialis et al, 2008). Electro-responsive or electrically stimulated pH sensitive polyelectrolyte membranes and hydrogels such as chondroitin 4-sulphate hydrogels (Jensen et al, 2002) and PMMA polyelectrolyte membrane (Grimshaw et al, 1990) have been suggested to be promising for the iontophoretic delivery of large charged macromolecules such as proteins and peptides.…”
Section: Introductionmentioning
confidence: 99%